tDCS for Memory Enhancement: Analysis of the Speculative Aspects of Ethical Issues - Voarino, Nathalie; Dubljević, Veljko; Racine, Eric (Frontiers in Human Neuroscience, 2017)
tDCS is a promising technology to enhance cognitive performance and memory function in healthy individuals. The early arrival of tDCS on the market for lifestyle uses and cognitive enhancement purposes lead to the voicing of some important ethical concerns, especially because there are no official guidelines or approval procedures to tackle these issues. The aim of this paper is to review ethical issues related to uses of tDCS for memory enhancement found in the ethics and neuroscience literature and to evaluate how realistic and scientifically well-founded these concerns are. We applied the methodological framework described by Racine et al. (2014) for “informed and reflective” speculation in bioethics. This framework could be succinctly presented as requiring: a) acknowledging assumptions more explicitly and identifying the value attributed to them, b) validating assumptions with interdisciplinary literature and c) adopting a broad perspective to support more comprehensive reflection. We identified four major considerations associated with the development of tDCS for memory enhancement: safety, autonomy, justice and authenticity. In order to assess the seriousness and likelihood of harm related to each of these concerns, we analyzed the assumptions underlying the ethical issues, and the level of evidence for each of them. It is generally more or less explicitly assumed in the literature that these factual assumptions exist or will come to exist. We identified seven distinct assumptions: prevalence, social acceptance, efficacy, ideological stance (bioconservative vs. libertarian), potential for misuse, long term side effects, and the delivery of complete and clear information. We conclude that ethical discussion about memory enhancement via tDCS sometimes involves undue speculation, and closer attention to scientific and social facts would bring a more nuanced analysis. At this time, the most realistic concern is related to violation of users’ autonomy by a breach of informed consent, as potential immediate and long-term health risks to private users remain unknown or not well defined. Clear and complete information about these risks must be provided to research participants and consumers of tDCS products or related services. Broader public education initiatives and warnings would be worthwhile to reach those who are constructing their own tDCS devices.